Zinc and Phosphorus Interaction on Growth and Nutrient Uptake by Wheat - Chaudhari, D S; Totawat, K L (Annals of Arid Zone, 2016)
A field experiment on zinc and phosphate fertilization to wheat was undertaken in rabi 1981-82 on a silty clay loam soil. Application of zinc and phosphorus alone or in combination recorded a significant increase in grain, straw and nutrient yield in wheat. Significantly highest yield of these parameters were recorded in phosphate fertilized plots when zinc was applied as foliar spray in conjunction with lime. Significant decrease in the concentration of zinc and phosphorus occured as a result of P and Zn fertilization, respectively. Soil application of ZnSO4 beyond 20 kg/ha level. resulted in significant decrease in yield of grain, straw and various nutrients.